2023
DOI: 10.2147/ccid.s398134
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Monocyte-to-High-Density Lipoprotein Cholesterol Ratio with Gastrointestinal Involvement of Immunoglobulin a Vasculitis

Abstract: Objective To illustrate the association of monocyte to high-density lipoprotein cholesterol ratio (MHR) and other serum indicators with the pathogenesis and prognosis of immunoglobulin A vasculitis (IgAV) patients in different subgroups. Methods A total of 158 adult patients and 113 healthy controls were enrolled, and the clinical presentation and laboratory indexes were comprehensively assessed. Results IgAV patients show significantly eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Clinical studies have shown that the platelet (PLT) counts, mean platelet volume (MPV), platelet-to-lymphocyte ratio, neutrophil-to-lymphocyte ratio (NLR), C3 level, D-dimer level, and low-density lipoprotein level are associated with gastrointestinal hemorrhage in HSP. [9][10][11] This is an important basis for doctors to diagnose the gastrointestinal bleeding status of HSP patients, which greatly aids clinical judgment. However, the etiology and pathogenesis of gastrointestinal bleeding in patients with HSP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that the platelet (PLT) counts, mean platelet volume (MPV), platelet-to-lymphocyte ratio, neutrophil-to-lymphocyte ratio (NLR), C3 level, D-dimer level, and low-density lipoprotein level are associated with gastrointestinal hemorrhage in HSP. [9][10][11] This is an important basis for doctors to diagnose the gastrointestinal bleeding status of HSP patients, which greatly aids clinical judgment. However, the etiology and pathogenesis of gastrointestinal bleeding in patients with HSP remain unclear.…”
Section: Introductionmentioning
confidence: 99%